Penyuluhan Kegawatdaruratan Pada Penyakit Kronis di Kelurahan Pedungan Puskesmas IV Denpasar Selatan - Sanjana, I Wayan Edi; Ni Putu Kamaryati; I Gede Edy Sagitha; Ni Kadek Sutini (Jurnal Pengabdian Kesehatan Masyarakat Mulawarman, 2023)
The elderly is likely to experience chronic diseases because there is a decrease in the function of organs in the body. An increase in life expectancy will correspond to an increase in the number of chronic disease sufferers, because every one elderly person has one or more chronic diseases. It is important for the elderly to understand the emergency conditions that may be experienced, because fluctuations in the condition of the elderly can occur in a short time. This Community Service aims to increase the understanding of the elderly regarding emergency conditions in chronic diseases. The method used is through counseling and pre and post tests to determine the understanding of the elderly. After the test was carried out, it was found that there was an increase in the average value of the participants' knowledge of emergency conditions in chronic diseases after being given counseling. With an increase in knowledge, it is hoped that patients will be able to perform first aid and find the right place for further help if chronic disease patients experience emergency conditions at home.